Rice Husk Silica-Coated Magnetic Particles As A Low Cost Support Material For Crude Pseudomonas Aeruginosa Lipase Immobilization - Noor Hindryawati (JURNAL KIMIA MULAWARMAN, 2016)
In this research, lipase produced from the bacteria Pseudomonas aeruginosa was immobilized on rice husk silica-coated Fe3O4 nanoparticles. The process included the following steps: preparation of magnetic ferrosoferric oxide nanoparticles (NP), coating NP with silica from rice husk ash, activation with glutaraldehyde and covalent immobilization of lipase on the support. The synthesis of the nanoparticle was followed by characterization through FT-IR, XRD, and FE-SEM. The hydrolysis kinetics (using 4-Nitrophenyl palmitate as a substrate) of the immobilized lipase followed Michaelis-Menten model with a Vmax and a Km value of 4.0 mM.s-1 and 0.63 mM, respectively. The immobilized lipase showed better tolerance to extreme temperature and pH compared to free lipase. About 60% of enzyme remained immobilized after ten cycles of reuse and 68.13% of it were stable until 49 days. Thus the silica-coated Fe3O4 nanoparticles appeared to be a potential support material for lipase immobilization applications.